Gest??o dos conflitos socioambientais de subsid??ncia de minas de carv??o em Santa Catarina: uma proposta de diretrizes para suporte ??s negocia????es - Corr??a, Rosany (2015)
This research aims to analyze environmental conflicts related to damage caused by surface subsidence from old coal mines in Crici??ma and its surroundings in the state of Santa Catarina. The theoretical model was developed taking the model developed by Rondeu (1996) - dealing with the dynamics analysis of conflicts - as a reference. The Rondeu??s model is presented as a tool to support the understanding and search of solutions to conflicts related to subsidence impacts of old underground mines mined out prior to 1988 on properties and structures. The development of the theoretical model allowed a better understanding of the origin and consequences of conflicts related to subsidence regarding perception and behavior of actors in clash and the solutions that have been forwarded over the years. This research is qualitative in nature and can be classified into three categories bibliographic, documental and field. The bibliographical search encompassed articles published in journals and in both national and international meetings on the following issues: coal mining, environmental and social impacts of subsidence, clashes involving different land uses, and management of environmental conflicts. The documentary research focussed on documents available in the websites of Federal Public Ministry and the Municipality of Crici??ma, as well as on documents provided by land-owners affected by environmental damage arising from coal mine subsidence. The field research was carried out via interviews with questions on environmental impacts, risk society, use of soil and subsoil, and environmental conflicts. In light of all information and evidence gathered, it can be concluded that conflicts resulting from subsidence of old mines, despite being relatively frequent in the region, are not always resolved taking into account all damages and losses involved, unless the final decision resulted from lawsuits. It is also possible to conclude that underground coal mining undertaken in the Crici??ma area prior to 1988 was conducted in a predatory way, leaving a legacy of fear and uncertainty to the local population. This scenario comes up because the population has no way to predict when and where subsidence of old mines will occur. In this regard, the inhabitants of Crici??ma and neighboring municipalities are facing constant risks that threaten their natural and built environment. The results of this research also indicate that the present situation in the Crici??ma area is worrisome because the Brazilian Federal State (who is responsible for managing the mining operation countrywide) is unable to manage conflicts arising from mining subsidence. As a final contribution the study presents a set of guidelines to support the negotiations related to environmental conflicts.